Why Are FGM Copulas Successful? A Simple Explanation - Songsak Sriboonchitta; Vladik Kreinovich (Advances in Fuzzy Systems)
One of the most computationally convenient nonredundant ways to describe the dependence between two variables is by describing the corresponding copula. In many applications, a special class of copulas—known as FGM copulas—turned out to be most successful in describing the dependence between quantities. The main result of this paper is that these copulas are the fastest to compute, and this explains their empirical success. As an auxiliary result, we also show that a similar explanation can be given in terms of fuzzy logic.